Molecular genetic mapping of the multiple endocrine neoplasia type 1 locus. - Pang, J; Pook, M; Eubanks, J; Jones, C; van Heyningen, V; Evans, G; Thakker, R (1992)
Familial multiple endocrine neoplasia type 1 (MEN 1) is an autosomal dominant disorder characterized by the combined occurrence of tumors of the parathyroid glands, the endocrine pancreas, and the pituitary gland. MEN 1 tumors have previously been shown to be associated with the loss of alleles on chromosome 11, and deletion mapping studies together with family linkage studies have localized the MEN 1 gene to 11q13. A detailed genetic map around the MEN 1 locus is required to facilitate further characterization and cloning of the gene (MEN1). We have characterized a panel of seven rodent-human somatic cell hybrids which contain fragments of human chromosome 11 with breakpoints in the pericentromeric region by using eight DNA sequences (D11S149, PGA, PYGM, D11S97, INT2, D11S37, D11S533, and D11S147) to define the region containing MEN1. This will facilitate the rapid localization of additional DNA sequences in this region. In addition, we have used a highly polymorphic repetitive degenerate hexanucleotide sequence, designated D11S533, for segregation studies in one family with MEN 1. These molecular genetic approaches will help to define a precise 1 to 2 centiMorgan map around MEN1.